The Effect of LC Learning Model Combined with Flow Chart to the Quality Process, Results Learning and Metacognitive Ability of Students - Suryati Suryati (Jurnal Pendidikan Sains, 2013)
Pengaruh Model Pembelajaran LC Dipadu Diagram Alir terhadap Kualitas Proses, Hasil Belajar dan Kemampuan Metakognitif Siswa Abstract: The reaction rate is one of the topics that are considered difficult by students. One alternative constructivist learning models that are expected to facilitate students in learning the topic is a model Learning Cycle (LC). LC phases are more effective when combined with a flow diagram. The purpose of this study is to determine the effect of LC learning model combined with a flow diagram of the process quality, learning outcomes and students' metacognitive skills chemistry. This study uses a descriptive design and a quasi-experimental design. The subjects are students of class XI IPA SMAN 2 Malang year 2010/2011. The results shows that: (1) the material reaction rate, the result of learning and metacognitive abilities of students that learned with a learning model LC combined flowchart higher compared with the results of learning and metacognitive abilities of students that learned with a learning model LC without flowchart, (2 ) on the material reaction rate, there are differences in learning outcomes are higher in students who have high academic ability compared with the learning outcomes of students who have low academic ability and there are no significant differences in metacognitive skills among students who have high and low academic ability, 3) there is no interaction effect combined learning model LC flow charts and academic ability for learning outcomes and metacognitive skills of students on the material reaction rate, (4) the material reaction rate, the quality of the learning process of students that learned with a learning model LC combined with a flowchart and learning model of LC without flowchart is progressing well. Key Words: LC, flow chart, metacognitive skills Abstrak: Laju reaksi merupakan salah satu pokok bahasan yang dianggap sulit oleh siswa. Salah satu alternatif model pembelajaran konstruktivistik yang diharapkan dapat memudahkan siswa dalam mempelajari topik tersebut adalah model pembelajaran Learning Cycle (LC). Fase-fase LC lebihefektif jika dipadu dengan diagram alir. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh model pembelajaran LC dipadu dengan diagram alir terhadap kualitas proses, hasil belajar dan kemampuan metakognitif kimia siswa. Penelitian ini menggunakan rancangan deskriptif dan rancangan eksperimen semu. Subjek penelitian ini adalah siswa kelas XI IPA SMAN 2 Malang tahun ajaran 2010/2011. Hasil penelitian menunjukkan bahwa: (1) pada materi laju reaksi, hasil belajar dan kemampuan metakognitif siswa yang dibelajarkan dengan model pembelajaran LC dipadu diagram alir lebihtinggi dibandingkan dengan hasil belajar dan kemampuan metakognitif siswa yang dibelajarkan dengan model pembelajaran LC tanpa diagram alir, (2) pada materi laju reaksi, terdapat perbedaan hasil belajar yang lebih tinggi pada siswa yang memiliki kemampuan akademik tinggi dibandingkan dengan hasil belajar siswa yang memiliki kemampuan akademik rendah dan tidak terdapat perbedaankemampuan metakognitif yang signifikan antara siswa yang memiliki kemampuan akademik tinggi dan rendah, (3) tidak terdapat pengaruh interaksi model pembelajaran LC dipadu diagram alir dengan kemampuan akademik terhadap hasil belajar dan kemampuan metakognitif siswa pada materi laju reaksi, (4) pada materi laju reaksi, kualitas proses pembelajaran siswa yang dibelajarkan dengan modelpembelajaran LC dipadu dengan diagram alir dan pembelajaran model LC tanpa diagram alir berlangsungdengan baik.Kata kunci: LC, diagram alir, kemampuan metakognitif